Hospital Stay Duration and Postoperative Complications among Patients Undergoing Volar Buttress Plate for Fixation in Volar Barton’s Fracture of the Distal Radius - Dr. Md. Khalilur Rahman (SSB Global Journal of Medical Science, 2023)
Introduction: Volar Barton’s fractures of the distal radius are complex injuries requiring precise surgical intervention to ensure optimal functional outcomes and minimize complications. This study investigates the hospital stay duration and postoperative complications among patients undergoing volar buttress plate fixation for these fractures. Objective: To evaluate the functional outcomes, hospital stay duration, and postoperative complications in patients treated with volar buttress plate fixation for Volar Barton’s fractures of the distal radius. Methods: This prospective interventional study was conducted at Tairunnessa Memorial Medical College & Hospital,Gazipur, Dhaka, Bangladesh over two years from March 2014 to September 2016. Thirty patients with closed Volar Barton’s fractures of the distal radius were included based on specific inclusion criteria. Data were collected using a pre-designed questionnaire and analyzed using the Sarmiento and Latta (1980) scoring system for functional outcomes. Results: The majority of participants were young adults aged 18-39 years (73%), with a male predominance (77%). Most fractures (63%) occurred on the left side. Eighty percent of patients received treatment within one week of injury. Hospital stays ranged from 1 to 8 days, with 53% of patients staying for 3-4 days. Postoperative complications were minimal, with 83% of patients experiencing no complications. Superficial wound infection was observed in 7% of patients, while other complications such as wrist stiffness, carpal tunnel syndrome, and late collapse each occurred in 3% of patients. At final follow-up, 80% of patients had satisfactory functional outcomes, with 73.3% achieving good results and 6.7% excellent. Conclusion: The volar buttress plate fixation technique for Volar Barton’s fractures of the distal radius demonstrates high efficacy in achieving satisfactory functional outcomes with minimal complications and manageable hospital stay durations. These findings support its continued use as a preferred surgical intervention for this type of fracture.